Full-spectrum extract from Cannabis sativa DKJ127 for chronic low back pain: a phase 3 randomized placebo-controlled trial - Karst, Matthias; Meissner, Winfried; Sator, Sabine; Keßler, Jens; Schoder, Volker; Häuser, Winfried (Nature medicine, 2025)
Chronic low back pain (CLBP) affects over half a billion people worldwide. Current pharmacologic treatments offer limited efficacy and carry substantial risks, warranting the development of safe and effective alternatives. This multicenter, randomized, placebo-controlled phase 3 trial evaluated the efficacy and safety of VER-01 in CLBP. It enrolled 820 adults with CLBP (VER-01, n = 394; placebo, n = 426) and included a double-blind 12-week treatment phase (phase A), a 6-month open-label extension (phase B), followed by either a 6-month continuation (phase C) or randomized withdrawal (phase D). The primary endpoint of phase A was a change in mean numeric rating scale (NRS) pain intensity, with a change in total neuropathic pain symptom inventory (NPSI) score as a key secondary endpoint in participants with a neuropathic pain component (PainDETECT > 18). The primary endpoint for phase D was time to treatment failure. The study met its primary endpoint in phase A, with a mean pain reduction of −1.9 NRS points in the VER-01 group (mean difference (MD) versus placebo = −0.6, 95% confidence interval (CI) = −0.9 to −0.3; P < 0.001). Pain further decreased to −2.9 NRS points in phase B, with effects sustained through phase C. The study also met its key secondary endpoint of phase A, with a mean NPSI decrease of −14.4 (standard error, 3.3) points from baseline in the VER-01 arm (MD versus placebo = −7.3, 95% CI = −13.2 to −1.3; P = 0.017). Although phase D did not meet its primary endpoint (hazard ratio = 0.75, 95% CI = 0.44-1.27; P = 0.288), pain increased significantly more with placebo upon withdrawal (MD = 0.5, 95% CI = 0.0-1.0; P = 0.034). In phase A, the incidence of adverse events—mostly mild to moderate and transient—was higher with VER-01 than with placebo (83.3% versus 67.3%; P < 0.001). VER-01 was well-tolerated, with no signs of dependence or withdrawal. VER-01 shows potential as a new, safe and effective treatment for CLBP. ClinicalTrials.gov registration: NCT04940741.